resistant or favorable? Chinese learners’ beliefs towarDs task-based language learning and teaChing - Le Gal, Damien; I-Chou, Pei (Íkala, Revista de Lenguaje y Cultura, 2015)
English as Foreign Language (EFL) in East Asia involves major sociocultural issues. Modern, Western-based methodologies such as Communicative Language Learning (CLL, Communicative Language Teaching, CLT in this paper) and its further development Task-Based Language Learning and Teaching (TBLLT, Ellis, 2003), feature principles which can conflict with some of the fundamental values of Confucian Heritage Cultures (CHC) education and hinder their adoption in Korea, Taiwan, Japan, Singapore, Hong-Kong and Vietnam. This article introduces a sociocultural, ethnographic perspective on EFL in East Asia which contextualizes language teaching in its broader educational and cultural environment. Teacher-centeredness, book and writing focuses, memorization strategies within a grammar-translation approach are in contradiction with modern language teaching methodologies’ focuses on learner-centeredness and teachers’ facilitating roles, student participation and interactions, communication competence and learner autonomy. The text advocates for a mean between Western and Eastern learning cultures through a context-based, culturally-sensitive approach and introduces classroom’s strategies for the implementation of CLL and TBLLT in China and East Asia.